(3eNJUQ GdefJXe hedJbW GdedJRes - (3YdGA GdOjf Hf eMeO Hf eSYhO GdgQhi , GdTgjQ HGdehdi eUfac GTGgQhOj GdHSWGejs; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3CeG HYO deG hbY fXQi ai OGQ GdSdWfI COQfg Ydi cJGH GdefJXe hhLOJg cJGHkG LGeYkG aGNJUQJg GNJUGQkG jbJVjg GdebGe s
(3BNQgG (B:s
(3BNQ GdehLhO efg ai JRhL YGFTI QVi Gddg YfgG s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B502 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B915 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B381 s
Keywords: (3GdJGQjNs